Association Between Incident Delirium Treatment With Haloperidol and Mortality in Critically Ill Adults*. Issue 8 (August 2021) - Duprey, Matthew S.; Devlin, John W.; van der Hoeven, Johannes G.; Pickkers, Peter; Briesacher, Becky A.; Saczynski, Jane S.; Griffith, John L.; van den Boogaard, Mark
Abstract : OBJECTIVES: Haloperidol is commonly administered in the ICU to reduce the burden of delirium and its related symptoms despite no clear evidence showing haloperidol helps to resolve delirium or improve survival. We evaluated the association between haloperidol, when used to treat incident ICU delirium and its symptoms, and mortality. DESIGN: Post hoc cohort analysis of a randomized, double-blind, placebo-controlled, delirium prevention trial. SETTING: Fourteen Dutch ICUs between July 2013 and December 2016. PATIENTS: One-thousand four-hundred ninety-five critically ill adults free from delirium at ICU admission having an expected ICU stay greater than or equal to 2 days. INTERVENTIONS: Patients received preventive haloperidol or placebo for up to 28 days until delirium occurrence, death, or ICU discharge. If delirium occurred, treatment with open-label IV haloperidol 2 mg tid (up to 5 mg tid per delirium symptoms) was administered at clinician discretion. MEASUREMENTS AND MAIN RESULTS: Patients were evaluated tid for delirium and coma for 28 days. Time-varying Cox hazards models were constructed for 28-day and 90-day mortality, controlling for study-arm, delirium and coma days, age, Acute Physiology and Chronic Health Evaluation-II score, sepsis, mechanical ventilation, and ICU length of stay. Among the 1, 495 patients, 542 (36%) developed delirium within 28 days (median [interquartile range] with delirium 4 d [2–7 d]). A total of 477 of 542 (88%) received treatment haloperidol (2.1 mg [1.0–3.8 mg] daily) for 6 days (3–11 d). Each milligram of treatment haloperidol administered daily was associated with decreased mortality at 28 days (hazard ratio, 0.93; 95% CI, 0.91–0.95) and 90 days (hazard ratio, 0.97; 95% CI, 0.96–0.98). Treatment haloperidol administered later in the ICU course was less protective of death. Results were stable by prevention study-arm, predelirium haloperidol exposure, and haloperidol treatment protocol adherence. CONCLUSIONS: Treatment of incident delirium and its symptoms with haloperidol may be associated with a dose-dependent improvement in survival. Future randomized trials need to confirm these results. Abstract : Supplemental Digital Content is available in the text.